Peran Imigrasi dalam Perkembangan Migrasi di Indonesia - Kamajaya, Andhika Putra Asmara; Rakasiwi, Abi Detrianto; Edgar, Arthur Cornelius (Universitas Batanghari Jambi, 2024)
This paper provides a comprehensive overview of migration patterns in Indonesia, covering both historical and modern movements. It covers a range of topics, including colonial migration, labor migration in the late 1900s and the present, as well as the difficulties faced by asylum seekers passing through the region and the effect on local government and coordination. The use of data collection methods including the examination of books or documents is usually categorized as a qualitative methodology. The main purpose of this data collection effort is to systematically gather pertinent information that will be used to strengthen the research variables and indicators. The Indonesian government views Indonesia primarily as a transit location for refugees, and not as a long-term settlement site. This implies that current measures do not provide adequate long-term protection for refugees. The lack of clear laws and regulations in Indonesia regarding refugees results in the absence of crucial social, economic, and cultural rights for this vulnerable population.